New Data for Endemic Phlomis cypria Post from North Cyprus: Biological Activities and LC MS/MS Analysis - Kunter, Imge; Tarabishi, Mohammed Tamim; Zabib, Niloufar; Ercetin, Tugba; Ilktac, Mehmet; Goger, Fatih; Kosar, Muberra (Assoc Pharmaceutical Teachers India, 2023)
Background: The genus Phlomis includes up to 100 species which are distributed throughout Eurasia. Of these species, Phlomis cypria Post (Lamiaceae) is an endemic plant from North Cyprus. P. cypria is commonly used in North Cyprus as medicinal herbal tea for the winter cold and flu. Phlomis species have antioxidant, antimicrobial and anticancer effects. Materials and Methods: In this study, herbal part of P. cypria from North Cyprus was sequentially extracted using hexane, dichloromethane and 70% aqueous methanol and using maceration at room temperature. All extracts were investigated for antiradical (DPPH? and ABTS+?), anticholinesterase, antibacterial and the cytotoxic activities and additionally, chemical compositions of the extracts were evaluated by LC MS/MS method. Results: Aqueous methanol extract showed antiradical activities (IC50 0.29 mg/mL in DPPH?; TEAC 1.22, 1.36 in ABTS+?) and cytotoxic activities (IC501264 mu g/mL on SK-HEP 1 cells). Dichloromethane extract only showed activity in anticholinesterase assay (inhibitions were 37.68% for AChE; 21.73% for BChE). Forsytoside B was found as the main phenolic compound in the active extract with caffeic acid bound to other compounds. Conclusion: According to the results, P. cypria could be a potential candidate as cytotoxic and cholineasterase inhibitor agent.
Keywords: Phlomis cypria; Lamiaceae; Antioxidant; Cytotoxicity; Antibacterial; Anticholinesterase